The bee Ruizanthedella mutabilis Spinola (Hymenoptera: Halictidae): a very common but poorly known species studied using integrative taxonomy - González-Vaquero, Rocío A.; Roig-Alsina, Arturo (Zootaxa, 2019)
Ruizanthedella mutabilis (Spinola) is a very abundant species in Chile and the northwest of Argentinean Patagonia. In this contribution, Halictus nigrocaeruleus Spinola 1851 is established as a junior synonym of R. mutabilis (Spinola 1851), after considering morphological data, DNA barcoding results, and biological observations. The variability in the colouration of the metasoma has been incorrectly used to distinguish these colour forms as valid species. New records enlarge the distribution of the species in Argentina, from the Andes to the Atlantic coast.